RISKS ASSESSMENT OF THE AUTOMATED INFORMATION SYSTEM - Корнієнко, Б.; Юдін, О.; Наконечна, Г. (Science-based technologies, 2012)
In given article it's presented an estimation of risks of information actives of the automated system of bank. It's made their classification and it's defined probabilities of realisation of probable threats.